2019
DOI: 10.1002/cctc.201901316
|View full text |Cite
|
Sign up to set email alerts
|

Confirming the Formation of Hydroxyl Radicals in the Catalytic Decomposition of H2O2 on Metal Oxides Using Coumarin as a Probe

Abstract: Hydrogen peroxide can be catalytically decomposed to O2 and H2O on metal oxide surfaces in contact with aqueous solutions containing H2O2. The initial step in this process has been proposed to be the formation of surface‐bound hydroxyl radicals which has recently been verified using tris as a radical scavenger. Here, we make use of the unique fluorescent product 7‐hydroxycoumarin formed in the reaction between hydroxyl radicals and coumarin to probe the formation of surface‐bound hydroxyl radicals. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…To exclude the specific presence of ⋅OH radicals in the blue‐LED driven oxidation of 1 to hydroperoxide 2 , the reaction was repeated in the absence of HRP using coumarin 3 b as a well‐recognized ⋅OH acceptor (“coumarin method”) (Figure 4). [53,54] In accordance with the literature, 3 b invariably reacts with ⋅OH at the C‐7 position of the aromatic ring to yield fluorescent derivative 3 a [55] . Under our experimental conditions no traces of 3 a were detected by HPLC analysis (Materials and methods and SI#4).…”
Section: Resultssupporting
confidence: 82%
“…To exclude the specific presence of ⋅OH radicals in the blue‐LED driven oxidation of 1 to hydroperoxide 2 , the reaction was repeated in the absence of HRP using coumarin 3 b as a well‐recognized ⋅OH acceptor (“coumarin method”) (Figure 4). [53,54] In accordance with the literature, 3 b invariably reacts with ⋅OH at the C‐7 position of the aromatic ring to yield fluorescent derivative 3 a [55] . Under our experimental conditions no traces of 3 a were detected by HPLC analysis (Materials and methods and SI#4).…”
Section: Resultssupporting
confidence: 82%
“…but not [OH]T when assessing AOPs. Although it has been suggested that coumarin is more useful as a qualitative probe for OH radicals [42], it may be employed quantitatively to determine [OH]1 with the appropriate deliberations. It is first established that coumarin reacts to form a variety of hydroxylation products upon contact with OH [43].…”
Section: Determination Of [Oh]1mentioning
confidence: 99%
“…[15] The formation of hydroxyl radicals in the catalytic decomposition of H 2 O 2 on ZrO 2 -powder in aqueous suspension has previously been demonstrated by tris and methanol, and quite recently by the use of coumarin as a probe. [16] In the latter case, the OH radicals react with coumarin mainly by addition, which eventually gives rise to a number of stable hydroxylated products. One of these, 7-hydroxycoumarin, is strongly fluorescent, and can for this reason be detected spectroscopically.…”
Section: Introductionmentioning
confidence: 99%